The pedagogical value of open Sankoré in teaching mapwork skills to grade 8 and 9 learners in a South African public school - De Almeida, Ines Galhardo (My University, 2018)
In the field of Geography, mapwork remains a subject where teachers experience many pedagogical barriers. The research considers the benefits of using ICT to lessen pedagogical problems that teachers face with mapwork skills in a Geography classroom. This research is based on understanding the pedagogical value of a smartboard software called Open Sankoré, in order to teach mapwork skills in Grade 8 and 9 Social Science. The research focuses on how Open Sankoré can benefit the teaching of mapwork skills not only for the Social Sciences but for FET Geography classrooms as well. The research draws on qualitative methods such as interviews and observations in one public school. Thereafter the research considers an in depth analysis of lessons and teacher interviews by drawing from frameworks such as Laurillard (2002) Conversational Framework (CF) and Innes (2009) definition of spatial competence. The CF allows for a better understanding of the value of Open Sankoré as an ICT teaching tool. Whereas Innes (2009) definition of spatial competence, assisted the research to explain the value of Open Sankoré as a geographical teaching tool. The conclusion was drawn from teacher’s experiences in relation to their training and teaching sessions with Open Sankoré. The research has highlighted that teacher’s experiences, values and beliefs of mapwork as well as ICT, play a significant role in understanding the value a ICT tool brings to teacher pedagogy. Teacher training must also be considered in order to understand the value the ICT tool brings to teacher pedagogy
A research project in partial fulfilment of a Master’s in Education Degree at the University of the Witwatersrand, Johannesburg, 2018
Keywords: Independent study-Study and teaching; Teaching-Aids and devices; Instructional materials centers-User education